Facile Extraction of Three Main Indole Alkaloids from Mitragyna speciosa by Using Hot Water. Issue 38 (8th October 2021) - Khunnawutmanotham, Nisachon; Chimnoi, Nitirat; Nangkoed, Phonchanok; Hasakunpaisarn, Anuch; Wiwattanapaisarn, Waraporn; Techasakul, Supanna
Abstract: The study presented a facile and efficient extraction method of main indole alkaloids from the fresh leaves of Mitragyna speciosa . A water extract containing three main indole alkaloids, namely mitragynine (MG), paynantheine (PT), and speciogynine (SG), was obtained by boiling the fresh leaves in water followed by partitioning with dichloromethane. The extraction yield of 1.0 % ( w/w ) was obtained under the optimized conditions. The contents of MG, PT, and SG obtained from water extraction were determined by high‐performance liquid chromatography analysis and were found to be comparable to those obtained from methanol extraction. However, because the extraction yield obtained from using methanol was tenfold higher than that from using hot water, this indicated the presence of some undesirable materials in the methanol but not in water extract. This method provided an alkaloid‐rich extract of M. speciosa . The procedure was easy to perform, inexpensive, environmentally benign, and could be easily scaled up from laboratory to industrial scale. Abstract : The present study demonstrated a facile and efficient extraction method of main indole alkaloids from the fresh leaves of Mitragyna speciosa . An alkaloid‐rich extract containing mitragynine and analogs was obtained by boiling the fresh leaves in water followed by partitioning with dichloromethane. The obtained extract was chlorophyll‐free, which would be either beneficial for further usage without purification or following easy purification. The method was facile as well as inexpensive and could be easily scaled up to industrial scale.